2023
DOI: 10.3390/ijms24119568
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Macrophages in Atherosclerosis: Pathophysiologic Mechanisms and Treatment Considerations

Abstract: Atherosclerotic diseases are a leading cause of morbidity and mortality worldwide, despite the recent diagnostic and therapeutic advances. A thorough understanding of the pathophysiologic mechanisms is thus essential to improve the care of affected individuals. Macrophages are crucial mediators of the atherosclerotic cascade, but their role has not been fully elucidated. The two main subtypes, tissue-resident and monocyte-derived macrophages, have distinct functions that contribute to atherosclerosis developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…The more the lesion progresses, the M2 will decrease and the M1 will increase in number. In addi?on, both M1 and M2 macrophages can change dynamically during the forma?on of atherosclerosis, and their subtypes can be one or another (Hou et al, 2023;Lin et al, 2021;Poznyak et al, 2021;Theofilis et al, 2023). In this study, IL-6 levels have decreased, but the number of foam cells is s?ll large, so it is possible that the macrophages containing foam cells are M2 macrophages, not M1, which can secrete IL-6.…”
Section: Discussionmentioning
confidence: 65%
“…The more the lesion progresses, the M2 will decrease and the M1 will increase in number. In addi?on, both M1 and M2 macrophages can change dynamically during the forma?on of atherosclerosis, and their subtypes can be one or another (Hou et al, 2023;Lin et al, 2021;Poznyak et al, 2021;Theofilis et al, 2023). In this study, IL-6 levels have decreased, but the number of foam cells is s?ll large, so it is possible that the macrophages containing foam cells are M2 macrophages, not M1, which can secrete IL-6.…”
Section: Discussionmentioning
confidence: 65%
“…Subsequently, uptake of LDL-C complexes leads to the formation of foam cells. In addition to plaque formation, macrophages are involved in extracellular matrix remodeling by secreting pro-inflammatory cytokines and chemokines [ 16 ]. In our study, the number of neutrophils and monocytes increased in patients with CAS compared with non-CAS patients, indicating that the higher the number of neutrophils and monocytes, the higher the incidence of CAS.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of photoactivation represents a promising alternative for the local treatment of atherosclerosis [96]. Recent studies have identified several new subtypes, e.g., including Mox, M(Hb), Mhem, M4 and HAMac of macrophages, that can be present in atherosclerotic plaques (Table 2) [101]. Several preclinical studies have suggested that effects of PDT using Photofrin ® is dependent upon the presence of neutrophils [102].…”
Section: An Antiatherogenic Photodynamic Therapymentioning
confidence: 99%